Harmonic Cancellation Technique of Four Pole Induction Motor Drive by Using Phase Shifted Carrier Space Vector PWM Technique - Kiran Nallamekala (Majlesi Journal of Electrical Engineering, 2024)
The voltage source inverter fed induction motor drive produces pulsating torque due to harmonics present in the output voltage of the inverter. Therefore reduction of harmonics is the major concern in any power converter fed ac drives. In this paper, a harmonic reduction technique for four pole induction motor drive is presented. A modified carrier based space vector PWM technique with suitable phase shift between modulating and carrier waves used to cancel the harmonic content in the output voltage. In order to use this PWM technique, stator winding of the four pole induction motor is disconnected exactly at middle and each part of the winding is fed with two two-level inverters from both the sides. All these two-level inverters are supplied by two isolated dc sources to avoid the path for zero sequence currents. By using proposed PWM technique to the inverter configuration, all lower order harmonics are shifted to four times switching frequency. The proposed concept is tested with 5hp four-pole induction motor in MATLAB/Simulink and experimentally also verified with laboratory prototype. Simulation and experimental results show the effectiveness of the proposed topology in complete linear modulation region and also demonstrate the improvement in harmonic profile.